2012
DOI: 10.1089/dia.2011.0243
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diagnosed and Undiagnosed Diabetes and Hypertension in India—Results from the Screening India's Twin Epidemic (SITE) Study

Abstract: Our study demonstrates that the substantial burden of diabetes and hypertension is on the rise in India. Patient awareness and timely diagnosis and intervention hold the key to limiting this twin epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
89
4
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 19 publications
7
89
4
5
Order By: Relevance
“…On the contrary, significant and positive association between family history of hypertension and hypertension occurrence was reported in other studies. 9,10,20 The lack of association in this study might be attributable to participants' ignorance of the hypertension status of their parents and families.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the contrary, significant and positive association between family history of hypertension and hypertension occurrence was reported in other studies. 9,10,20 The lack of association in this study might be attributable to participants' ignorance of the hypertension status of their parents and families.…”
Section: Discussionmentioning
confidence: 75%
“…This is comparable to a prevalence of 39.6% found in a similar study conducted in rural areas of Northern state, Sudan, 10 in the US (39.4%), 18 and interestingly, similar to that previously recorded among Nuba and Coptic ethnic groups inhabiting RNS. 19 This prevalence is higher than the rates recorded in India (22.2%) 20 and lower than those found in Ghana (83%). 21 The high prevalence of undiagnosed hypertension in this study could be attributed to a variety of factors, including but not limited to: increasing urbanization, dietary changes, increasing life stress and possibly to some genetic factors.…”
Section: Discussionmentioning
confidence: 77%
“…This is much higher than the observation by Zaman, M. M., et al in their study which found 17% of adults to be obese. 13 A multicentric study in India by Joshi, S. R., at al (19)., Central obesity was prevalent among 32.8% males and 56.1% females and 115 (10.9%) had body mass index ≥27.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Contrary to this several workers reported a higher prevalence of hypertension. [17][18][19][20][21][22][23] Lower prevalence of hypertension has been observed by some researchers. [24][25][26][27] The result of the present study shows an increase in prevalence of hypertension with an increase in age.…”
Section: Discussionmentioning
confidence: 99%